Filthy rich fae - Lee, Geneva (Amara, an imprint of Entangled Publishing LLC, 2024)
"Cate Holloway knows the unspoken rule of New Orleans: avoid the powerful Gage crime family at all costs. Of course, that was before her brother got caught in their chaos. Now Cate has no choice but to confront the dark and forbidding prince of New Orleans himself and beg for her brother's life. But Lachlan Gage is as lethal as he is beautiful...and the only currency he's interested in is her soul. Because Lachlan isn't just some ruthless criminal. He's fae. And he has his own secret reasons for binding her to him. Tricked and desperate, Cate is torn between humanity and the breathtaking Otherworld. A place filled with shadows and secrets, with members of each fae court plotting against her just as her captor's motives for trapping her become more mysterious. And if she can't break this sinister bargain in the next thirty days, she'll be bound to the inscrutable yet infuriatingly tempting fae prince and his deadly world...forever"--